Crises, arguments et médiatisations numériques - Gloria Awad (Communication)
The author studies the dual gradation (value and contact) of crises as journalistic events. She examines the digital mediatizations of crises using the Peircean definition of the argument as a sign for future programming or retrodiction. This makes it possible to highlight a prospective empirical dimension that is characteristic of contemporary crises and their expectative contingency.